1996
DOI: 10.1103/physrevc.53.1562
|View full text |Cite
|
Sign up to set email alerts
|

High-spin states inTe121,122: Identification of favored noncollective oblate states

Abstract: High-spin states up to Iϳ20ប have been studied in the 121,122 Te nuclei using the 116 Cd( 9 Be,xn͒ reaction at 37.8 MeV. In this spin regime, several favored noncollective oblate states (␥ϭϩ60°), where the singleparticle angular momenta generate the total nuclear spin, are predicted to coexist with weakly deformed collective structures. Theoretical expectations for such oblate states, based on TRS cranking calculations, are compared to the experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…122 Te exhibits a non-vibrational state already at the three-phonon level. The breakdown of the collective behavior is a consequence of competing single- particle motion, know to exist in tellurium isotopes [75][76][77][78][79][80], and signaled in 122 Te by the unusual energy ratios E(4 + 1 )/E(2 + 1 ) < 2 and E(6 + 1 )/E(4 + 1 ) < 1.5 [81]. The alignment of both valence nucleons and protons promoted across the Z = 50 shell gap breaks the spherical symmetry and give rise to non-collective deformed states.…”
Section: Energy Spectra With Quantified Uncertaintiesmentioning
confidence: 99%
“…122 Te exhibits a non-vibrational state already at the three-phonon level. The breakdown of the collective behavior is a consequence of competing single- particle motion, know to exist in tellurium isotopes [75][76][77][78][79][80], and signaled in 122 Te by the unusual energy ratios E(4 + 1 )/E(2 + 1 ) < 2 and E(6 + 1 )/E(4 + 1 ) < 1.5 [81]. The alignment of both valence nucleons and protons promoted across the Z = 50 shell gap breaks the spherical symmetry and give rise to non-collective deformed states.…”
Section: Energy Spectra With Quantified Uncertaintiesmentioning
confidence: 99%
“…1. The positiveparity ground band was established up to I π = 10 + and 12 + in investigations by Chowdhury et al [21] and Lee et al [22], respectively, and was later extended up to I π = 16 + by Paul et al [19]. Nag et al [20] reported positive-parity levels up to I = (25) and several side branches.…”
Section: Results and Level Schemementioning
confidence: 98%
“…The level scheme of 122 Te, based on both present and previous results [19,20], is displayed in Fig. 1.…”
Section: Results and Level Schemementioning
confidence: 98%
See 2 more Smart Citations